From Miniscule Biomedical Models To Sexuality's Depths - Nyanzi, Stella (The Lancet, 2006)
Nearly three decades of prevention interventions against HIV/AIDS have yielded little eff ect, with the few success stories heralded universally as potential blueprints in best-practice dossiers. Unprotected sex is still the most common mode of HIV transmission. Unintended or teenage pregnancies, sexually transmitted infections including HIV/AIDS, and sexual abuse, violence, and discrimination remain major public-health challenges, despite targeted strategies of redress. What is missing in available sexual-health programmes, policies, and activism? Why are they not as eff ective as they promise? What is wrong with these interventions? One possibility is foundational: interventions are premised on limited working defi nitions of sexuality as a concept